2015
DOI: 10.2139/ssrn.2740663
|View full text |Cite
|
Sign up to set email alerts
|

The Food-Energy-Water Security Nexus: Definitions, Policies, and Methods in an Application to Malawi and Mozambique

Abstract: 1.1 Conceptual framework of the FEW nexus 2.1 Per capita production in Malawi, Mozambique, and SSA regions 2.2 Daily protein supply in Malawi, Mozambique, and Southern Africa 2.3 Energy supply in Malawi, Mozambique, and Southern Africa 2.4 Types of cooking stoves: clay, rocket, and three-stone traditional 2.5 Comparison of fuelwood consumption and cooking time for cooking stoves 2.6 Distribution of cookstove programs in Africa south of the Sahara, 1984-2010 3.1 Circular flow of income in an economy 3.2 Ex ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 107 publications
0
19
0
Order By: Relevance
“…The review of the workthat explicitly mentions the nexus and Mozambique (Bullock and Hülsmann, 2015;Nielsen et al, 2015) revealed an essentially water centric Nexus analysis, i.e., water is the main focal point of analysis and intervention. Bullock and Hülsmann (2015) identify a high, but unevenly distributed, potential for sustainable development based on hydropower for Mozambique and several vulnerabilities.…”
Section: Explicit Nexus Analysis Made On Mozambique and Southern Africamentioning
confidence: 99%
See 4 more Smart Citations
“…The review of the workthat explicitly mentions the nexus and Mozambique (Bullock and Hülsmann, 2015;Nielsen et al, 2015) revealed an essentially water centric Nexus analysis, i.e., water is the main focal point of analysis and intervention. Bullock and Hülsmann (2015) identify a high, but unevenly distributed, potential for sustainable development based on hydropower for Mozambique and several vulnerabilities.…”
Section: Explicit Nexus Analysis Made On Mozambique and Southern Africamentioning
confidence: 99%
“…Moreover, for Bullock and Hülsmann (2015), emphasize the role of Integrated Water Resources Management to bring about synergetic effects on the nexus. Nielsen et al (2015) conducted a nexus analysis on Mozambique to identify trade-offs. Interactions and possible synergies to justify and model the effect of a number of specific interventions in the nexus.…”
Section: Explicit Nexus Analysis Made On Mozambique and Southern Africamentioning
confidence: 99%
See 3 more Smart Citations